Cannibalism in psychotic disorder: a rare case presentation - Dogan, Mehmet (The journal of forensic psychiatry & psychology, 2024)
The aim of this study is to investigate the phenomenon of cannibalism in psychotic disorders through a case presentation. According to the statement obtained after the incident, a 35-year-old female patient claimed that she killed her mother by slitting her throat at the request of spiritual entities. She then decapitated her mother’s head and boiled it in a pot. She also mentioned eating pieces of flesh that had been cut off her leg, while keeping some pieces in the fridge. The results of psychometric tests indicated paranoid features on the Rorschach, together with evidence of personality organisation at a psychotic level. In addition, MMPI test results showed above-normal scores on the Hysteria subtest, indicating psychotic deviation, and on the Paranoia subtest, suggesting abnormality in these areas. The psychiatric examination revealed moderate self-care skills and limited emotional expression, as well as paranoid ideation and persecutory delusions within thought content. In addition, observations noted the patient’s difficulties with goal-directed thinking and cognitive functioning, including attention span, calculation, judgment, and abstract reasoning. Based on these findings, the individual received a diagnosis of ‘psychotic disorder (schizophrenia)’ and was deemed not criminally responsible. In forensic psychiatric evaluations of such cases, it is important not to overlook the potential contribution of psychometric testing alongside clinical examination, as cannibalism should be considered as a possible manifestation of psychosis.